2009
DOI: 10.1111/j.1365-2222.2009.03379.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with a modified birch pollen extract in allergic rhinoconjunctivitis: clinical and immunological effects

Abstract: Immunotherapy with a modified slow-release birch pollen extract, administered in a single-strength preparation with a rapid dose increase, is safe and efficacious. IgG and IgG4 antibodies against native Bet v 1 are induced, which block basophil activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…As shown in our study, the suppressive effect of the therapy on basophil activation at the end of treatment and at the peak of the grass pollen season after treatment further supports the powerful immunogenicity of allergoids. Some studies have shown that sera containing therapy-induced allergen-specific IgG can suppress basophil activation [20,26,27,28]. In this study, we reported a pronounced increase of allergen-specific IgG4 after immunotherapy.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As shown in our study, the suppressive effect of the therapy on basophil activation at the end of treatment and at the peak of the grass pollen season after treatment further supports the powerful immunogenicity of allergoids. Some studies have shown that sera containing therapy-induced allergen-specific IgG can suppress basophil activation [20,26,27,28]. In this study, we reported a pronounced increase of allergen-specific IgG4 after immunotherapy.…”
Section: Discussionsupporting
confidence: 64%
“…However, there are several studies showing the increment of specific IgG antibodies by allergoid immunotherapy [22,26,27]. As shown in our study, the suppressive effect of the therapy on basophil activation at the end of treatment and at the peak of the grass pollen season after treatment further supports the powerful immunogenicity of allergoids.…”
Section: Discussionsupporting
confidence: 59%
“…Some authors describe reduction in basophil activation following AIT possibly due to serological factors [Ceuppens et al 2009;Aasbjerg et al 2014;Ozdemira et al 2014;Schmid et al 2014]. Van Overtvelt and Gomez failed to demonstrate the effects of AIT on basophil activation following AIT [Van Overtvelt et al 2011;Gomez et al 2015].…”
Section: Cellular Changesmentioning
confidence: 99%
“…Studies have shown that clinical efficacy is retained using modified allergen extracts at higher doses and that modified preparations are considered safer than nonmodified allergen extracts [1,2,3,4]. …”
Section: Introductionmentioning
confidence: 99%